What hope for the future? GNAQ and uveal melanoma. Issue 5 (3rd March 2011) - Sisley, Karen; Doherty, Rachel; Cross, Neil A
Abstract : Uveal melanomas (UM) are aggressive ocular tumours that spread to the liver. They are characterised by alterations of chromosome 3 and 8, which are highly predictive of a poor prognosis. Unfortunately, being able to identify those patients with aggressive disease has not, as yet, translated into improved survival. Recently, mutations of guanine nucleotide-binding protein G(q) subunit alpha ( GNAQ, or G-alpha-q), which effectively turn it into a dominantly acting oncogene, have been identified in approximately half of UM. These mutations are specific to UM and other non-cutaneous melanomas, and are not found in normal tissues, thus making them potential therapeutic targets. Here, the authors review the background to GNAQ in UM and explore what makes it such an interesting target for the future treatment of patients.